PENGEMBANGAN SUMBER DAYA MANUSIA PADA MASYARAKAT KABUPATEN WAKATOBI - Ninik Endang Purwati; Lili Yanas (Journal Publicuho, 2022)
This study aims to determine the development of human resources in the community of Wakatobi regency by the Marine and Fisheries Service of Wakatobi Regency. This research is a field research, the informants in this study are 8 people consisting of the Head of the Marine and Fisheries Service of Wakatobi Regency, treasurer of the Office, The Field of Education and Training and Assistance of the Marine and Fisheries Service of Wakatobi Regency, as many as 2 people, the Field of Development of Aquaculture And Fish Hatchery Areas as many as 1 person, the people of Wakatobi Regency as participants in education and training in the development of human resources  as many as 2 people.  The data collection technique in this study is that data collection can be obtained from the results of interviews, document studies, and combined or triangulation. The type of research used in this study is a type of qualitative descriptive research. Based on the results of the study, it was concluded that this education and training was very useful and had an effect on the development of knowledge, community skills, in planning, preventing, facing and minimizing weather changes that affected farmers and the harvest increased by providing training education and assistance to the community in groups who were concerned about the improvement of community cooperation.